Policy Brief : Pengolahan Abu Hasil Pembakaran Limbah Medis sebagai Alternatif Pengganti Bahan Bangunan yang Berasal dari Fasilitas Pelayanan Kesehatan - Muhammad Fadli Ramadhansyah; Arief Nugroho; Nur Endah Wahyuningsih (Fakultas Teknik, 2021)
Policy briefs have an important role in solving problems that exist in a health agency, especially during the COVID-19 pandemic. One example of the problems that exist in health care facilities is air pollution that comes from the ashes resulting from the burning of medical waste. The impact of air pollution on humans is that it triggers respiratory disorders which are characterized by a decrease in the elasticity of the lungs to accommodate the volume of air so that this can be associated with the incidence of respiratory disorders. In addition, it has a small particle size and is scattered in the air in large quantities. The purpose of this study is to provide information related to the summary of policy making that is used as a reference to increase the effectiveness of processing ash from combustion based on a review study. This study uses a descriptive method with a literature review approach. The criteria for the articles used have a publication time of the last 10 years, discuss the utilization of combustion ash, and discuss the policy of processing incinerator ash waste. Making a policy brief can be used as a starting point for advocating for local governments to use ash from burning as an alternative to building materials to reduce air pollution and the accumulation of ash waste that accumulates in incinerators in health care facilities.